PENGKAJIAN PENGEMBANGAN TEKNOLOGI SATELIT UNTUK TUJUAN PERTAHANAN DAN KEAMANAN - Bakara, Jakondar; Susanto, Susanto (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2012)
ABSTRACT. Satellite technology in the world was originally developed by the United States and the Soviet Union (Russia) for the interests of defense and security (military). Afterwards, other countries also developed this technology, among others, China, India, Japan, Israel, and Indonesia. Indonesia is currently developing a satellite called LAPAN TUBSAT Generation-2 with the mission of surveillance (surveillance satellite), which can be applied for military purposes. Various satellite capabilities are already developed by many countries. Recently United States has developed Geo Eyesatellite, the worlds most advanced satellite with a very highresolution. With the rapid advancement of this technology available in developed countries, the satellite technology with surveillance mission can be applied for defense and security interests in Indonesia to maintain state sovereignty.